2013
DOI: 10.1088/1367-2630/15/4/045024
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of GeV-scale electron acceleration in a gas-filled capillary discharge waveguide

Abstract: The generation of GeV-scale electron beams in a gas-filled capillary discharge waveguide with good reproducibility is discussed. Beams of electrons with energies above 900 MeV, and with root-mean-square divergences of 3.5 mrad, are observed for a plasma density of 2.2 × 10 18 cm −3 and a peak input laser power of 55 TW. The variation of the maximum electron energy with the plasma density is measured and found to agree well with simple models. Injection and acceleration of electrons at the to date lowest plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Interaction of the relativistic laser pulse with large-scale NCD-plasmas ensures a long acceleration path and results into effective coupling of the laser energy into energetic electrons. Experiments on the electron heating by a 80-100 J, 750 fs short laser pulse of 2-5×10 19 W cm −2 intensity demonstrated that the effective temperature of supra-thermal electrons increased from 1.5-2 MeV, in the case of the relativistic laser interaction with a metallic foil at high laser contrast, up to 13 MeV for the laser shots onto the pre-ionized 300-500 μm long foam layer with a NCD. The measurements showed high directionality of the acceleration process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction of the relativistic laser pulse with large-scale NCD-plasmas ensures a long acceleration path and results into effective coupling of the laser energy into energetic electrons. Experiments on the electron heating by a 80-100 J, 750 fs short laser pulse of 2-5×10 19 W cm −2 intensity demonstrated that the effective temperature of supra-thermal electrons increased from 1.5-2 MeV, in the case of the relativistic laser interaction with a metallic foil at high laser contrast, up to 13 MeV for the laser shots onto the pre-ionized 300-500 μm long foam layer with a NCD. The measurements showed high directionality of the acceleration process.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, up to 60% of the laser energy was concentrated in the focal spot with a FWHM-size of 14±1×19±1 μm 2 . Shot-to-shot deviations of the laser energy and 30% uncertainties in the laser pulse duration resulted in the rather large confidential interval of the laser intensities ranging from 2.1 up to 5.1×10 19 W cm −2 . The corresponding normalized vector potentials are a L =3.9-6.0.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…femtosecond) e-beams [25]. Besides, polychromatic (or 'comb-like') beams from an LPA, with the current modulated on a femtosecond scale, have been observed in experiments [26][27][28][29]. Simulations indicate that such beams readily lend themselves to all-optical manipulation, promising generation of spectrally controlled quasi-monochromatic, femtosecond γ-ray pulses, or trains of pulses with a femtosecond synchronization [9][10][11].LPAs, however, face a number of challenges, one of which is preservation of beam quality, that is, elimination of a high-charge, low-energy tail, which develops when acceleration is continued through electron dephasing [30][31][32][33][34].…”
mentioning
confidence: 96%
“…femtosecond) e-beams [25]. Besides, polychromatic (or 'comb-like') beams from an LPA, with the current modulated on a femtosecond scale, have been observed in experiments [26][27][28][29]. Simulations indicate that such beams readily lend themselves to all-optical manipulation, promising generation of spectrally controlled quasi-monochromatic, femtosecond γ-ray pulses, or trains of pulses with a femtosecond synchronization [9][10][11].…”
mentioning
confidence: 99%